2021
DOI: 10.3389/fpsyg.2021.653848
|View full text |Cite
|
Sign up to set email alerts
|

Help Is in Your Blood—Incentive to “Double Altruism” Resolves the Plasma Donation Paradox

Abstract: Blood donation is considered as one of the purest forms of altruism. Plasma donation, in contrast, despite being a similar process, is mostly a paid activity in which donors are compensated for their contribution to the production of therapeutic preparations. This creates a so-called “plasma paradox:” If remuneration is promised for a socially useful effort, volunteers with altruistic motives might be deterred. At the same time, regular plasma donors who pursue the monetary benefits of donation might drop out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Altruistic blood donation indicates respect for the need of others and the importance of life, which in turn engenders a sense of social responsibility and benefits the whole community. 39,40 It also helps protect the poorest sector of society from exploitation, and may help ensure the safety of blood supplies, since payments could incentivize some people to hide relevant medical information such as infectious diseases. 39,40 However, with regard to product safety, in the USA, where remuneration is allowed, there have been no reported cases of infectious diseases transmitted from plasma donors since the modifications of the Code of Federal Regulations requirements and adoption of the Plasma Protein Therapeutics Association IQPP standards.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Altruistic blood donation indicates respect for the need of others and the importance of life, which in turn engenders a sense of social responsibility and benefits the whole community. 39,40 It also helps protect the poorest sector of society from exploitation, and may help ensure the safety of blood supplies, since payments could incentivize some people to hide relevant medical information such as infectious diseases. 39,40 However, with regard to product safety, in the USA, where remuneration is allowed, there have been no reported cases of infectious diseases transmitted from plasma donors since the modifications of the Code of Federal Regulations requirements and adoption of the Plasma Protein Therapeutics Association IQPP standards.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…In this scenario, payments are made for plasma donations, but people are offered the opportunity to transfer the payment to a charity/nongovernmental organization, thus encouraging donors who may wish to keep the payment as well as those who would prefer to donate the money. 40 A recent study found an increased willingness to donate plasma when "double altruism" was an option. 40 It is also worth noting that incentives need not be cash payments.…”
Section: Rivera and Lozanomentioning
confidence: 99%
See 3 more Smart Citations